OBTAINED IN CATTLE POISONING VETERINARY SANITARY EXAMINATION OF PRODUCTS (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article describes the interpretation of the literature on the poisoning of cattle with pesticides, chloroorganic compounds with strongly acting substances, the elimination of products from infected animals from veterinary sanitary equipment.